Molecular ecology - Freeland, Joanna; Kirk, Heather, 1980-; Petersen, Stephen (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2011)
Molecular Ecology, 2nd Edition provides an accessible introduction to the many diverse aspects of this subject. The book takes a logical and progressive approach to uniting examples from a wide range of taxonomic groups. The straightforward writing style offers in depth analysis whilst making often challenging subjects such as population genetics and phylogenetics highly comprehensible to the reader. The first part of the book introduces the essential underpinnings of molecular ecology and gives a review of genetics and discussion of the molecular markers that are most frequently used in ecolo.
Cover; Title Page; Copyright; Preface; Acknowledgements; Chapter 1: Molecular Genetics in Ecology; What is Molecular Ecology?; The Emergence of Molecular Ecology; An Unlimited Source of Data; Overview; Chapter Summary; Useful Websites and Software; Chapter 2: Molecular Markers in Ecology; Understanding Molecular Markers; Modes of Inheritance; Molecular Markers; Overview; Chapter Summary; Useful Websites and Software; Further Reading; Chapter 3: Genetic Analysis of Single Populations; Why Study Single Populations?; Quantifying Genetic Diversity; What Influences Genetic Diversity?; Overview.
Includes bibliographical references (pages 395-432) and index.
Print version record.
Keywords: Molecular ecology; NATURE -- Ecology; NATURE -- Ecosystems & Habitats -- Wilderness; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Ecology; Molecular ecology; Molekularbiologie; Ökologie; Electronic books